Plant-based dietary approach to stage 3 chronic kidney disease with hyperphosphataemia. Issue 12 (23rd December 2019) - Campbell, Thomas M; Liebman, Scott E
Abstract : A 69-year-old man with type 2 diabetes, hypertension and stage 3 chronic kidney disease (CKD), hyperphosphataemia and borderline hyperkalaemia presented to an office visit interested in changing his diet to improve his medical conditions. He adopted a strict whole-foods, plant-based diet, without calorie or portion restriction or mandated exercise, and rapidly reduced his insulin requirements by >50%, and subsequently saw improvements in weight, blood pressure and cholesterol. His estimated glomerular filtration rate (eGFR) increased from 45 to 74 mL/min after 4.5 months on the diet and his microalbumin/creatinine ratio decreased from 414.3 to 26.8 mg/g. His phosphorus level returned to the normal range. For individuals with CKD, especially those with obesity, hypertension, or diabetes, a strict, ad libitum whole-food, plant-based diet may confer significant benefit, although one must consider potential limitations of a creatinine-based GFR equation in the face of significant weight loss.